Drugs, causes, species, effects - Jalil Ismael, Dunya (International Journal of Psychosocial Rehabilitation, 2020)
The problem of drug use of all kinds is one of the problems that have become a serious threat at both levels: individual and social, and this problem has emerged and worsened with the complexity of circumstances and increased psychological pressures and economic burdens at the Arab and global levels. Drugs are a recent social problem coming and delegations in this intensive form on Iraq to the growing number of users, the size of drugs, and the increased demand for them from different categories and segments, in response to the factors of change that are taking place Middle East, of which Iraq is part; the new culture, which blew its winds on this society after the American occupation of Iraq in 2003 and the resulting liberation; Border control and prohibitions, the new cultural wind emanating from Iraq’s neighboring countries, some of which are producers and other drug consumers, and the last smuggler to a people spread among its circles unemployment, lack of jobs, and its continued suffering from the burden of wars and scourges that passed through it—all these things, along with other reasons, led to the growing problem of drug use in Iraq (Al-Ali, 2002, p. 10).